Regulation of actin cytoskeletal dynamics in T cell development and function - Lam, Trang T.; Chong, Mark M. W. (Frontiers in Immunology, 2025)
T cell development and function depend on precise remodeling of the actin cytoskeleton, which regulates migration, cell division, immunological synapse formation, and signal transduction. Regulators of actin include nucleators (Arp2/3, Formins) and binding proteins (coronins, cofilin, myosin) that orchestrate cytoskeletal dynamics to ensure efficient antigen recognition and signaling, while Rho GTPases (Rac1, Cdc42, RhoA) link extracellular cues to actin rearrangements, influencing both conventional T cell activation and function. Dysregulated actin dynamics contribute to immunodeficiencies and autoimmunity, and thus understanding how the actin cytoskeleton is regulated in T cells has important implications.